(untitled) (Management and Connections Journal, 2013)
DOI: http://dx.doi.org/10.13071/regec.2317-5087.2013.2.2.4647.102-122 Analyzing the structure to hire engineers for technological activities in Brazil is the purpose of this article, which investigates whether the participation of these professionals in P & D in the processing industry has grown. For this, we used the data provided by the Technological Innovation Research (PINTEC). Information allows us to observe the evolution of the effort in P & D and the participation of engineers among the professionals dedicated to the technological activities. Despite the expectation of a structure which strengthens technological activities, with a greater demand for engineers, data show that industry is not constructing a more intensive structure having engineers or P & D activities as a basis.